Peer Teaching Process in English Subject at SMPN 4 Langsa - Mutia Handayani (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
The focus of this study is an attempt to figure out the peer teaching process inEnglish subject in pandemic situation at SMPN 4 Langsa. Peer teaching methodis a teaching method for delivering subject material with the peers’ help. In thisresearch, the researcher used phenomenology approach of qualitative research.The process of collecting data was done by applying the interview, observationand questionnaire. The questionnaires were conducted to 30 respondents from theeighth-grade students at SMPN 4 Langsa, while the interview and observationwere conducted to 4 respondents from the eighth grade students at SMPN 4Langsa who have the roles as peer tutor. Result showed that Peer teachingprocess began when the students have problems in learning English with theirEnglish teacher. It was revealed that the peer teaching showed a good implicationin order to get an effective learning process in English subject. the researchersuggested to the eighth-grade students at SMPN 4 langsa have to improve theirskill in English and realize their own learning method in order to increase andstimulate them in learning English in the teaching learning process.